2020
DOI: 10.1111/evj.13313
|View full text |Cite
|
Sign up to set email alerts
|

Environmental persistence of equid herpesvirus type‐1

Abstract: Background Equid herpesvirus type 1 (EHV‐1) is ubiquitous in equine populations causing respiratory disease, and complications including late‐term abortion and neurological disease. Eradication of EHV‐1 from housing environments that typically contain unsealed wood and porous bedding materials can be challenging. However, consideration should be given to take advantage of the viral envelope's susceptibility to environmental conditions. Objective To determine environmental persistence of EHV‐1 on materials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…The results from this study indicate that EHV stability on fomites is largely dependent on the surface it comes into contact with and that it can remain infectious up to 42 days after exposure. A recent study showed that EHV-1 can remain viable in the environment on materials such as leather, fabric, wood shavings, wheat straw, and polystyrene for at least 48 h [ 13 ]. It is unclear if animals can contract EHV infections from contaminated surfaces, which likely depends on the breed or species, dose of virus shed, exposure of virus to environmental factors such UV radiation and desiccation, and frequency of animal interaction with such surfaces.…”
Section: Transmission By Fomitesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results from this study indicate that EHV stability on fomites is largely dependent on the surface it comes into contact with and that it can remain infectious up to 42 days after exposure. A recent study showed that EHV-1 can remain viable in the environment on materials such as leather, fabric, wood shavings, wheat straw, and polystyrene for at least 48 h [ 13 ]. It is unclear if animals can contract EHV infections from contaminated surfaces, which likely depends on the breed or species, dose of virus shed, exposure of virus to environmental factors such UV radiation and desiccation, and frequency of animal interaction with such surfaces.…”
Section: Transmission By Fomitesmentioning
confidence: 99%
“…At present, very few studies on the effect of physicochemical factors on viability of EHVs in the environment are available [ 13 , 22 , 41 ]. Therefore, in order to prevent EHV spreading in captive or domestic equids, disinfection of surfaces may be recommendable under certain circumstances.…”
Section: Detection Of Viral Shedding In the Wild On Fomites Using Swabsmentioning
confidence: 99%
“…Further, the detection of EHV-1 by qPCR did not allow drawing any conclusions regarding the contagiousness of these horses. A recent study determined that irrespective of the environment–material evaluated (leather, polyester-cotton fabric, pinewood shavings, wheat straw, and plastic), viable virus could still be recovered at 48 h following standard inoculation with EHV-1 [ 25 ]. An additional study showed that EHV-1 remained stable and infectious in water for up to three weeks [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…EHV-1 is purportedly environmentally labile and does not survive well outside its equine host; it should, therefore, be easily killed by treatment with detergents, lipid solvents, heat and common disinfectants. Saklou at al., however, showed that EHV-1 can survive 48 h on environmental material [ 15 ]. Experimentally, the virus has survived for up to a week at ambient temperatures when dried into paper, wood and rope and up to 35 days on horsehair and burlap [ 16 ].…”
Section: Methodsmentioning
confidence: 99%